Socio-Economic and Demographic Determinants of Food Poverty among Household Heads: Evidence from a Zanzibar Household Budget Survey - Balan, Ramkumar T (Asian Journal of Health Research, 2025)
Introduction: Food poverty and insecurity among household members have negative consequences on nutritional quality and may result in inadequate nutrition, endangering the physical, emotional, and financial well-being of household members. In 2024, Zanzibar was classified as IPC Phase 3 (Food Crisis) in five regions of the island. Previous studies in Tanzania often used food consumption score and food insecurity experience as measure of food consumption and hence food poverty. It was inadequate, and food consumption for an adult per month or per day (in kilocalories) was used. Material and Methods: 2788 household heads of HB Survey were used. Objective of the study was to investigate the socio-economic and demographic variables that affect household heads' access to food in Zanzibar. Fixing 2200kc as baseline consumption (equal to 1571.1091 TSH), food poverty was estimated among adults in Zanzibar.  Stratum was based on areas and weighted with occupancy. Two stage stratified design binary logistic model was executed, and AUC under ROC curve was used to evaluate the exactness of the model. Results: Descriptive statistics on covariates of poverty were determined, and food poverty and non-food poverty were estimated. There are significant differences in employment status, food poverty, pre-primary schooling, and age groups in the data, but no significant difference was found between rural and urban areas in terms of food poverty. Conclusion: Household size, educational level of householder, total monthly expenditure, and location were the significant correlates found influencing poverty.